Oral salt and water versus intravenous saline for the prevention of acute kidney injury following contrast-enhanced computed tomography: study protocol for a pilot randomized trial. Issue 1 (December 2015) - Swapnil, Hiremath; Knoll, Greg; Kayibanda, Jeanne; Fergusson, Dean; Chow, Benjamin; Shabana, Wael; Murphy, Erin; Ramsay, Tim; James, Matthew; White, Christine; Garg, Amit; Wald, Ron; et al.
Abstract Background Although intravenous saline is the accepted prophylactic measure for the prevention of contrast- induced acute kidney injury, the oral route could offer an equivalent, practical, and cost saving approach. A systematic review of randomized trials that compared oral versus intravenous volume expansion for the prevention of radiocontrast-induced nephropathy in patients receiving arterial contrast reported no significant difference in the risk of contrast induced acute kidney injury between the oral and intravenous arms. Most trials for contrast nephropathy prevention have been in the setting of arterial contrast such as with cardiac catheterization, and not with venous contrast, such as computed tomography. The aim of this paper is to describe the protocol of a pilot trial comparing the effect of oral salt and water versus intravenous saline on the prevention of Acute Kidney Injury following contrast-enhanced computed tomography. Methods Our study is a pilot, single-centre parallel randomized controlled trial. To be included, participants must be at stage 4 of chronic kidney disease as defined by a glomerular filtration rate <30 mL/min/1.73 m2, aged greater than 18 years and to undergo an outpatient contrast-enhanced computer tomography of the chest or abdomen. A total 50 patients will be randomised to receive either oral salt and water or intravenous isotonic saline. The primary outcome is feasibility, including estimates of recruitment rate, adherence to intervention and completeness of follow-up to assist in planning the definitive trial. The secondary outcome is safety and includes adverse events with oral salt and water loading as compared to intravenous isotonic saline. Discussion The results of this pilot trial will provide critical information to plan a definitive trial to test the efficacy of the route of volume loading regimens in prevention of acute kidney injury after contrast-enhanced CT scans. Trial registration The trial is registered at the US National Institutes of Health (ClinicalTrials.gov) #NCT02084771 . Abrégé Contexte L'administration prophylactique de solution saline par voie intraveineuse est utilisée pour la prévention de l'insuffisance rénale aiguë (IRA) secondaire aux produits de contraste iodés (PCI). Cependant, une administration par voie orale pourrait être un traitement alternatif équivalent, pratique et économique. Une revue systématique des essais cliniques à répartition aléatoire, qui comparaient les volémies post-administration orale, d'une part, et intraveineuse, d'autre part, de solution saline dans la prévention des néphropathies secondaires aux PCI de patients qui recevaient un agent de contraste par voie artérielle, a été effectuée. Aucun écart significatif en matière de risque d'IRA secondaire aux PCI n'a été observé entre les deux groupes à l'étude. La plupart des essais traitant de prévention des néphropathies secondaire aux PCI ont été effectués en contexte d'administration artérielle, comme par cathétérisme cardiaque, et non d'administration veineuse, comme par tomodensitométrie. Le but de cet article est de décrire le protocole d'un essai comparatif pilote des effets d' une solution saline administrée par voie orale à ceux d'une solution saline isotonique administrée par voie intraveineuse dans la prévention de l'insuffisance rénale aiguë secondaire à la tomodensitométrie avec injection d'agent de contraste. Méthode Notre étude est un essai comparatif pilote, unicentrique, à répartition aléatoire. Seuls les participants atteints de maladie rénale chronique de stade 4, définie par un débit de filtration glomérulaire < 30 ml/min/1, 73m2, âgés de plus de 18 ans, et devant subir une tomodensitométrie avec agent de contraste du thorax ou de l'abdomen en clinique externe, pourront faire partie de l'échantillon. L'administration d'eau salée par voie orale ou de solution saline isotonique par voie intraveineuse sera répartie aléatoirement sur 50 patients. Les premières conclusions de l'étude aideront à planifier l'essai définitif. Celles-ci concernent la faisabilité, dont les estimations du taux de recrutement, d'adhésion à l'intervention et d'achèvement du suivi. Les conclusions secondaires se rapportent à la sécurité et font part, entre autres, d'une comparaison des effets indésirables de l'administration orale d'eau salée et de l'administration intraveineuse de solution saline isotonique. Discussion Les résultats de cet essai pilote fourniront de l'information cruciale pour la planification de l'essai définitif visant à tester l'efficacité des voies d'administration des traitements de prévention d'IRA après les tomodensitométries avec agent de contraste.